Type 3 vasa previa with no low-lying placenta, with central umbilical cord insertion at the upper uterine segment, and with aberrant vessels on the broad membrane: A case report - Michihisa Shiro; Masumi Kiyose; Yukiko Suzuki; Yuka Sano; Shota Ikagawa; Shigeki Yoshida (Case Reports in Women's Health, 2023)
Type 3 vasa previa is a new concept. Herein, a case is reported of a 35-year-old woman, pregnant following in vitro fertilization, in whom vasa previa was detected on color Doppler ultrasound at 26 weeks, with no finding of a low-lying placenta. A cesarean section was performed at 34 weeks and 3 days. Gross examination of the placenta showed Type 3 vasa previa with findings somewhat different from previous reports: two aberrant fetal vessels with branching on the broad membrane, and central cord insertion which was farther from the longitudinal center of the placenta than were the running vessels on the membrane. Vasa previa cannot be excluded due to normal cord insertion at the upper uterine segment, absence of placenta previa, or a low-lying placenta in the second trimester. Careful ultrasound screening can promote neonatal survival in patients with Type 3 vasa previa.